The Management Business: LA PROJECT Business Planning Using The Business Model Canvas (BMC) From Processed Waste Furniture Production Become Kitchenware Products - Yustitia, Moeri; Deni Saputra, S.T., M.Sc. (Adpebi Science Series, 2022)
The high interest in the furniture and handicraft industry has led to a surge in demand for furniture and handicrafts, which has made business players compete to increase the quality and quantity of their production. The high demand has also resulted in an increase in the amount of waste from furniture production, but many companies/business actors are still unable to handle this production waste properly. This research is qualitative and aims to know and review readiness in making business plans from processed furniture production waste by using the elements of creating a business model canvas. Data collection techniques used are observation, interview documentation, and literature study. After the data is collected, it is processed using source triangulation. Based on the results of the research, things that can be used as a reference in creating a business here is by stating the readiness of planning from all segmentation according to the method taken, namely the business model canvas here, the production waste is processed into kitchenware, namely cutlery products or multipurpose kitchen needs from processed wood waste